Transcutaneous bilirubinometry during and after phototherapy in preterm infants: a prospective observational study - Raba, Ali Ahmed; O'Sullivan, Anne; Miletin, Jan (BMJ paediatrics open, 2020)
Objective: To examine the accuracy of transcutaneous bilirubinometry (TCB) measurements during and after phototherapy (PT) in preterm infants. Design: Prospective observational cohort study. Setting: Level III neonatal centre. Patients: Preterm infants (from 23+0 to 36+6 weeks of gestation) born between June 2017 and May 2018 requiring PT. Interventions: TCB was measured from an exposed area of the skin (the sternum; TCBU) and the covered area of the skin under the nappy (the bony part of the upper outer quadrant of the buttock; TCBC) within an hour of obtaining total serum bilirubin (TSB). Main outcome measures: Correlation and agreement between TCB (TCBU and TCBC) and TSB during and after PT. Results: We have enrolled 196 preterm infants. There was a significant correlation between TSB and TCB during PT (r=0.72, 95% CI 0.66 to 0.77 in covered area; r=0.75, 95% CI 0.70 to 0.80 in uncovered area) and after PT (r=0.87, 95% CI 0.83 to 0.91). TCB underestimated TSB level during PT, with a mean TCBC-TSB difference of -25±43 (95% agreement limits of 62 to -112) and a mean TCBU-TSB difference of -48±46 (95% agreement limits of 45 to -140). The agreement between TCB and TSB after cessation of PT improved, with TCB underestimating TSB by a mean TCB-TSB difference of -10±31 (95% agreement limits of 52 to -72). Conclusion: TCB measurements correlated strongly with TSB levels during and after PT. However, there was a wide and clinically relevant disagreement between TCB and TSB measurements during the PT phase, improving significantly after PT.